Vaginal candidiasis among women of reproductive age in Dnipro city (Ukraine): Species spectrum of Candida and their susceptibility to antimycotics - O. M. Starishko; Y. S. Voronkova; T. H. Ostanina; O. S. Voronkova (Regulatory Mechanisms in Biosystems, 2019)
Candidiasis is one of the most common pathological processes, especially among women of reproductive age, especially pregnant. It can be expressed as Candida carriage and as an active form of infection. Although candidiasis is caused by opportunistic microorganisms, its effects can be quite significant, so it is necessary to treat it with the use of antimycotic drugs. In view of the spread among these microorganisms of resistance to antimicrobial drugs, the determining factor for the success of therapeutic measures, it is important to make a preliminary assessment of the susceptibility to antimycotics of strains isolated from persons with Candida carriage or active candidiasis. The aim of the research was to study the species range of fungi of the genus Candida isolated from the reproductive tract in women with dysbiosis and to study their susceptibility to antimycotics. Total of 227 samples of biological material from women aged 16 to 56 years have been investigated. Microscopic and cultural methods of detecting of fungi in the primary material were used for research. For the identification of species of Candida fungi, a polymerase chain reaction method in real-time was used. It was determined that the frequency of detection of Candida fungi in the composition of vaginal microbiome during inflammatory pathological processes was 76.7%. It was shown that the incidence of Candida carriage – 51.7% – slightly exceeded the frequency of detection of the active form of infection – 48.3%. The species spectrum of pathogens included: C. albicans (57.1%), C. krusei (12.6%), C. glabrata (19.5%) and Candida spp. (16.1%). In the case of active form of infection, C. albicans was prevalent – 64 (76.2%) cases. In the case of Candida carriage, other species were prevalent – 58 (64.4%) cases. The most effective drug against all isolates was amphotericin B – more than 87% of isolates were susceptible. The least effective drug was nystatin: less than 60% of isolates were susceptible. There is a rather high level of resistance to certain antimycotic drugs among the Candida species, which requires a prior preliminary study of the susceptibility of isolated strains to antimycotics for the purpose of choosing a rational and effective treatment scheme.